Rencana Pengembangan Kawasan Wisata Berbasis Kearifan Lokal Pada Area Pasca Tambang Timah di Kecamatan Merawang Kabupaten Bangka - Rifqi Adi Nugraha; Afra Donatha Nimia Makalew; Syartinilia (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
Environmental damage due to tin mining in Bangka Regency, especially in Merawang District is increasing. The negative impacts of this mining are eliminating the composition or structure of vegetation, changing the function of wildlife habitat, changing the shape of the landscape, producing waste, and draining ground and surface water. One form that can be developed in the development of post-tin mining areas that are environmentally friendly is the development of tourism based on local wisdom while still paying attention to natural resources, especially conservation areas such as protected forests and borders. Tourism development is carried out to restore the area with various activities that involve the community. The results of spatial analysis of tourism suitability in Merawang District have very suitable criteria (S1) with tourism suitability index (IKW) of 67.29% and suitability (S2) with IKW value of 19.82% and not suitable (S4) with IKW value of 12, 89%. Local wisdom in Merawang District is based on AHP analysis in the ecological aspects of